Pengaruh Literasi Keuangan terhadap Pengelolaan Keuangan Pelaku Usaha Tani di Kota Makassar - Suharyadi Rahmat; Nurdiana Nurdiana; Muhammad Hasan; Nurjannah Nurjannah; Ratnah S (Ideas Publishing, 2023)
This Financial Literacy Research is a research that uses a quantitative descriptive quantitative method. This study used 30 respondents where all of these respondents. The results obtained in this study indicate that there is a significant effect of financial literacy on financial literacy financial management. This can be seen from the results of the statistical analysis of the data used, where financial literacy shows a partial effect on financial management. after testing the coefficient of determination, the results show that financial literacy affects financial management by 15.4%, while the other 84.6% is influenced by other factors not examined.